2020
DOI: 10.1016/j.pedneo.2019.09.007
|View full text |Cite
|
Sign up to set email alerts
|

Current status of enterovirus D68 worldwide and in Taiwan

Abstract: Enterovirus D68 was first identified in 1962 and caused a worldwide outbreak starting from the North America in 2014. Enterovirus D68 has been in continuous circulation among many countries recently, including Taiwan. Reports also reveal high seroprevalence, which indicates that the disease burden of enterovirus D68 may be underestimated via viral culture or polymerase chain reaction results. Although most infected cases have mild respiratory illness, severe complications including acute flaccid myelitis and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 51 publications
1
8
0
Order By: Relevance
“…EV-D68 was detected in 16 (2.8%) patients from 3 countries: Guinea (11/391), Niger (1/85), and Senegal (4/59). The detection of EV-D68 in fecal samples from AFP patients in West Africa countries is consistent with case reports and case series from the United States, South America, Asia, and Europe during the same period (7)(8)(9)(10)(11).…”
supporting
confidence: 87%
See 1 more Smart Citation
“…EV-D68 was detected in 16 (2.8%) patients from 3 countries: Guinea (11/391), Niger (1/85), and Senegal (4/59). The detection of EV-D68 in fecal samples from AFP patients in West Africa countries is consistent with case reports and case series from the United States, South America, Asia, and Europe during the same period (7)(8)(9)(10)(11).…”
supporting
confidence: 87%
“…Phylogenetic analysis of the viral protein 1 fragment revealed that all sequences from West Africa belonged to clade B, subclade B3 (Figure 2). Indeed, EV-D68 subclade B3 was the predominant strain reported in several global regions during the same period (9)(10)(11)(12)(13)(14). Moreover, results from phylogenetic testing showed that EV-D68 strains in West Africa clustered with strains circulating in Spain (GenBank accession no.…”
mentioning
confidence: 99%
“…The 2014 United States outbreak increased global awareness of EV‐D68, resulting in a rise of worldwide surveillance and seroprevalence studies. Studies from Japan, 14 the Netherlands, 15 Taiwan, 16,17 and the United Kingdom 9 also showed a rise in NAbs pre‐ and post‐Sept 2014. This suggests a global upsurge of EV‐D68 infection.…”
Section: Discussionmentioning
confidence: 94%
“…13 The 2014 United States outbreak increased global awareness of EV-D68, resulting in a rise of worldwide surveillance and seroprevalence studies. Studies from Japan, 14 the Netherlands, 15 Taiwan, 16,17 and the United Kingdom By analogy with EV-A71, NAbs against EV-D68 are likely to provide protection from infection or at least symptomatic disease. 18 Overall, the low seroprevalence rate in children (age…”
Section: Discussionmentioning
confidence: 99%
“…Starting with sporadic clusters of acute respiratory infections around the world in the 2000s [ 4 , 5 , 6 , 7 ], EV-D68 caused an outbreak with at least 1395 confirmed cases in the US in 2014 [ 8 ] and was associated with acute flaccid paralysis [ 9 ]. Infections were also reported in Canada, Argentina, Norway, Netherlands, France, Germany and Taiwan [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ]. EV-D68, thus emerged as a neuro-invasive viral pathogen as it caused epidemics in 2016 and 2018 in the US [ 18 , 19 ] and worldwide [ 14 , 15 , 20 , 21 , 22 , 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%